2003
DOI: 10.1007/s00256-003-0635-z
|View full text |Cite
|
Sign up to set email alerts
|

The value of water-excitation 3D FLASH and fat-saturated PDw TSE MR imaging for detecting and grading articular cartilage lesions of the knee

Abstract: FS PDw TSE is an accurate method for detecting, grading and sizing articular cartilage lesions of the knee and yielded superior results relative to WE 3D FLASH MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
59
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 24 publications
3
59
0
2
Order By: Relevance
“…However, the disadvantages of these sequences are a high sensitivity to susceptibility artefacts and a limited visualisation of the subchondral bone, menisci and ligaments [21,54,55]. Previous reports also showed that 1.5 T MRI with fat-suppressed fast spin-echo proton-density-weighted sequences can be used to evaluate the cartilage of the knee with accuracy comparable to that of other cartilage-specific sequence protocols [21,56,57]. In the current study, we used fat-saturated proton-density-weighted fast spinecho sequences with a 3-mm slice thickness in transverse, sagittal and coronal planes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the disadvantages of these sequences are a high sensitivity to susceptibility artefacts and a limited visualisation of the subchondral bone, menisci and ligaments [21,54,55]. Previous reports also showed that 1.5 T MRI with fat-suppressed fast spin-echo proton-density-weighted sequences can be used to evaluate the cartilage of the knee with accuracy comparable to that of other cartilage-specific sequence protocols [21,56,57]. In the current study, we used fat-saturated proton-density-weighted fast spinecho sequences with a 3-mm slice thickness in transverse, sagittal and coronal planes.…”
Section: Discussionmentioning
confidence: 99%
“…Mohr et al [28] compared fat saturated 2D PD TSE sequences to water-excitation 3D fast low angle shot (WE 3D FLASH), but found the conventional 2D TSE to be superior to the 3D sequence. Welsch et al [12] compared 3D SPACE in PD-weighting, isotropic 3D true-fast-imaging with steady-stateprecession (True-FISP) and conventional 2D MR sequences in the observation of cartilage repair tissue in 37 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Secuencias 3D FSE (Fast Spin Echo) con resolución isotrópica corresponden a otro método promisorio para reemplazar las secuencias 2D en la práctica clínica. Secuencias 3D FSE permiten obtener imágenes en densidad protónica, la secuencia más comúnmente utilizada en RM músculo-esquelética (7,(8)(9)(10)(11)(12)(13)(14)(15)(16) . La gran ventaja de esta secuencia es su resolución espacial, siendo posible obtener reconstrucciones multiplanares en ejes arbitrarios, hecho que favorece la interpretación (Figura 4).…”
Section: Discussionunclassified